Review the Social and Political Factors Affecting the Trend of New Religious Movements (Case Study: Two Movements Eckankar and Elijah Ramallah) - jafar hezarjaribi; hassan farahani (توسعه اجتماعی)
Although religion has always played a part in the community cohesion and contributes to the convergence of groups and individuals, but the new cult of religious causes divisions in the community as well as deepening and intensification of social fissures. The aim of this study was to investigate the social and political factors affecting the trend in new religious movements. The procedure, cross-correlation and the target application. The population consisted of followers and converts the new religious movements in the city of Tehran. The target group of this study is among the supporters of the two movements "Eckankar and Elijah Ramallah" was chosen as the experimental group considered that the group's total number of 44225 people, the sample size was calculated based on a sample of 400 people. Instruments measure in this study was a questionnaire designed to assess the relationship of Pearson correlation coefficients and variables to explain the impact of single and multi-variable regression analysis and path analysis were used. Summary results of the study suggest that the changing pattern of reference, the hegemonic political system and orientation of new religious movements is a significant relationship.